THE GENESIS OF THE DEVELOPMENT OF THE CONTRACTUAL AND LEGAL FOUNDATIONS OF REAL ESTATE ALIENATION - Rahimjonov, Akmaljon (Oriental Journal of History, Politics and Law, 2026)
This article provides a comprehensive analysis of the legal foundations governing contractual relations related to the alienation of real estate (including sale and purchase, donation, exchange, annuity, lifelong maintenance agreements, and other transactions) in the context of a market economy. The author examines the impact of constitutional, legislative, and institutional reforms aimed at protecting private property, liberalizing civil transactions, and promoting digitalization in the Republic of Uzbekistan on the regulation of real estate transactions. Particular attention is given to the content of the right to private property as enshrined in the 2023 Constitution of the Republic of Uzbekistan, the international standards established by the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights, as well as the influence of the UNIDROIT Principles, including the principles of freedom of contract, binding force of contracts (pacta sunt servanda), and good faith, on the national legal system.